THE EFFECT OF A COMBINATION OF SHEN-MEN EAR POINT ACUPRESSURE AND BABY MASSAGE ON BABY SLEEP QUALITY - Engkus, Nurhayati Binti; Cusmarih, Cusmarih (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: Newborn babies spend more time sleeping with an average sleep duration of 16 – 17 hours a day. Low quality sleep can interfere with the baby's growth, make the body's immune function vulnerable, and disrupt the regulation of the endocrine system. Objective: to determine the effect of the combination of Shen-men ear point acupressure and baby massage on the quality of baby's sleep. Method: Design research used _ is pretest-posttest design. Population study This is all over mother who has baby aged 3-12 months with amount sample as many as 37 mothers. Variable data retrieval quality Sleep baby use Pediatric Sleep Questionnaire (PSQ) questionnaire. Data analyzed using the average comparison test paired sample t test statistics. Results: Average score quality Sleep baby before treatment k combination Shen-men ear acupressure and massage is 9.11. Average score quality Sleep baby after treatment k combination Shen-men ear acupressure and massage is 6.16. There is influence a combination of Shen-men ear point acupressure and baby massage on the quality of baby sleep in the working area Health Center Batujaya Subdistrict Batujaya Regency Karawang, p-value 0.000 < 0.05.